2022
DOI: 10.21608/ejrs.2022.268253
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bee Venom and Oxytetracycline on Blood Parameters, Antioxidant, Immunity Status and Bacterial Count of Weaning Rabbits

Abstract: The present study aimed to compare the effects of bee venom (BV) and Oxytetracycline (OXY) supplementation on blood biochemical analysis, antioxidant, immunity status and bacterial count of weaning rabbits. Sixty Californian male rabbits at 35 days of age with average body weight of 589±90 g were randomly divided into five equal groups (12 for each); 1 st group (control) was given water (placebo), 2 nd group (OXY; 1g/l water), 3 rd , 4 th , and 5 th groups were received BV at (2, 4 and 8 mg/kg body weigh/day, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In the current investigation, we reported the antibacterial potential of BV at three distinct concentrations (2, 4 and 8 mg/kg BV) against TBC, E. coli and its favourable impacts on the beneficial Lactobacilli. Remarkably, the antibacterial activity of BV, even at these concentrations, surpassed that of the standard antibiotic oxytetracycline administered at a dosage of 1 g/L of drinking water, as reported in recent literature (El-Speiy et al, 2022).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the current investigation, we reported the antibacterial potential of BV at three distinct concentrations (2, 4 and 8 mg/kg BV) against TBC, E. coli and its favourable impacts on the beneficial Lactobacilli. Remarkably, the antibacterial activity of BV, even at these concentrations, surpassed that of the standard antibiotic oxytetracycline administered at a dosage of 1 g/L of drinking water, as reported in recent literature (El-Speiy et al, 2022).…”
Section: Discussionsupporting
confidence: 69%
“…Increased activity of these enzymes indicates an improved antioxidant capacity (Meister & Anderson, 1983). in line with these mechanisms, El‐Speiy et al (2022) reported that the observed elevation in the activities of plasma glutathione peroxidase (GSH‐Px) and SOD suggests an augmentation in the antioxidant capacity.…”
Section: Discussionmentioning
confidence: 91%
“…[47] Injecting up to 2 mg/kg of body weight/day Improves antioxidant status, immunity, and bacterial count in the hindgut of weaning rabbits. [48] Injected at 0.3 mg/rabbit twice a week from 5 to 10 weeks of age Improves feed conversion ratio, body weight, and carcass quality of growing rabbits. [49] In ovo injection of 10 µg of melittin/egg on day 18 of incubation Increases the post-hatch chick's weight and enhances the immunological indices.…”
Section: Bee Products Administration and Dose Main Results Referencesmentioning
confidence: 99%
“…It can also improve rabbits' blood biochemical parameters (such as liver enzyme activities) and antioxidant activity (such as glutathione S-transferase and glutathione peroxidase), as well as their immunological indices (such as IgA, IgG, and IgM) [46,47]. According to El-Speiy et al [48], using bee venom up to 2 mg/kg body weight/day can improve immunological and antioxidative activities while decreasing harmful microorganisms in the hindgut of weaning rabbits. Bee venom has a positive influence on some biochemical parameters such as total protein, albumin, and globulin concentration in animal blood, as well as stimulating liver enzyme activity (aspartate and alanine aminotransferase) [99].…”
Section: Bee Venommentioning
confidence: 99%
“…Instead, the study by El-Speiy et al (2022) investigated the possibilities of supplementing bee venom (BV) to the drinking water of rabbits [ 86 ]. The association of BV with oxytetracycline (OXY) was proposed in an experimental group of investigation.…”
Section: Effects and Applications In Veterinary Medicinementioning
confidence: 99%